The effect of Promotion, Driver Service Quality, Price Discounts and Postage Discounts on Purchasing Decisions of SME’s Gempolklutuk Village - Arasy Alimudin; Agus Sukoco; Ani Wulandari; Elok Damayanti; Siti Yunqanzun (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: This study aims to determine the effect of promotions, service quality drivers, price discounts and shipping costs discounts on purchasing decisions using the service SME’s Gempolklutuk Village to students in Surabaya. Design/methodology/approach: This study used quantitative research, testing the hypothesis. The number of samples in this study were 100 respondents, namely consumers who had purchased using the services of UKM Gempolklutuk Village. The data source used is primary data obtained from questionnaires. This study uses multiple linear regression analysis. Findings: The results of the study stated that Promotion, Driver Service Quality, Price Discounts and Shipping Cost Discounts had a significant influence simultaneously on Purchase Decisions. Promotional variables, Driver Service Quality, Price Discounts and Shipping Cost Discounts have a partially significant effect on Purchase Decisions. The results of the coefficient of determination test concluded that the value of Adjusted R Square Promotion, Driver Service Quality, Price Discounts and Shipping Cost Discounts amounted to 57.3% of the Purchase Decision variable and the remaining 42.7% was influenced by other variables not examined in this study. Research limitations/implications: The limitations of this research problem are the influence of promotions, driver service quality, price discounts and shipping fee discounts on purchasing decisions by using online delivery services from the MSME platform in Gempolklutuk Village. Paper type: Research paper